Adaptive ability to cope with atypical or novel situations involving tool use: An fMRI approach. (January 2015) - Wakusawa, Keisuke; Sugiura, Motoaki; Sassa, Yuko; Jeong, Hyeonjeong; Yomogida, Yukihito; Horie, Kaoru; Sato, Shigeru; Yokoyama, Hiroyuki; Kure, Shigeo; Takei, Noriyoshi; Mori, Norio; Kawashima, Ryuta
Highlights: We examined neural mechanisms for coping with atypical or unexperienced situations. The left parietal region plays a role in structuring basic adaptive action. Regions linked to processing situations are activated for action coordination. The left frontal region plays core roles in coordination of action for coping. The right frontal region functions during switching a concept of action adaptively. Abstract: We investigated the neural mechanisms underlying the ability to cope in atypical or novel situations using tools. We hypothesized that two cognitive components support this ability: adaptive coordination (for adapting to situational demands) and cognitive inhibition (for inhibiting the incongruent actions afforded by tools). We had subjects choose novel tools for a given task or choose among familiar tools in an atypical situation, during which we examined cortical activation in their brains using functional magnetic resonance imaging. Neural activation during adaptive coordination was observed in the left lateral orbitofrontal cortex, inferior frontal gyrus and sulcus, middle and medial frontal gyrus, intraparietal sulcus, precentral sulcus, inferior temporal gyrus, supramarginal gyrus, the bilateral insula, anterior cingulate cortex, and the right callosal sulcus. Activation indicating cognitive inhibition was observed in the right middle and inferior frontal gyrus. These findings demonstrate that the left parietal region shapes basic action, whereas the right frontal region inhibits stereotypical action. The left frontal regions are thought to be linked to the processing of ambiguous actions and play key roles in coordinating actions, whereas other regions are involved in processing situational contexts. Our results may be important for understanding the neural systems underlying adaptability to daily social situations.